2020
DOI: 10.1155/2020/6059346
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of General Dental Practitioners and Specialists about Emergency Management of Traumatic Dental Injuries in Qassim, Saudi Arabia

Abstract: Context. Studies about knowledge of emergency management of traumatic dental injuries (TDIs) which affect children by general dental practitioners (GDPs) and specialists in Saudi Arabia are lacking. Aim. The aim of this cross-sectional study was to assess the knowledge level of GDPs and specialists about TDI emergency management and its relation with demographic variables in Qassim region, Saudi Arabia. Materials and Methods. A random sample of 239 GDPs and specialists was given a two-part questionnaire; the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…However, their knowledge regarding the management of extrusive luxation did not seem to be satisfactory, as only 35% of participants knew the correct management, and only 26.7% of participants knew the correct management of lateral luxation injury. Such findings coincide with those of the study of Al-Haj Ali et al, who reported inadequate knowledge of general practitioners and dental specialists regarding the management of luxation injuries [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, their knowledge regarding the management of extrusive luxation did not seem to be satisfactory, as only 35% of participants knew the correct management, and only 26.7% of participants knew the correct management of lateral luxation injury. Such findings coincide with those of the study of Al-Haj Ali et al, who reported inadequate knowledge of general practitioners and dental specialists regarding the management of luxation injuries [14].…”
Section: Discussionsupporting
confidence: 91%
“…International Journal of Dentistry low to moderate, with an overall mean knowledge score of 3.421 ± 0.49. Similarly, many previous studies have reported the lack of knowledge about the management of dental trauma among dental practitioners [12][13][14][15]. e results also revealed that gender and the year of study had no significant effect on the mean knowledge score.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the studies conducted in two different regions of Nepal, the dentists were asked the following question: ''Should the avulsed teeth be replanted?” to which 86%, and 31% of the participating dentists replied: “No” ( 11 , 18 ). In similar studies conducted in China and Saudi Arabia, the rates of the “No” answer were 87% and 85% respectively ( 17 , 23 ), whereas in the present study, 92% answered “No”. Holan and Shmueli ( 19 ) in 2003, reported that 50% of the dentists in Israel told that avulsed permanent teeth should not be replanted, and 8% said that they had no idea.…”
Section: Discussioncontrasting
confidence: 60%
“…However, Abu-Dawoud et al ( 7 ) and Al-Haj Ali et al . ( 23 ) reported that dentists stated that milk was the best storage medium for avulsed teeth. In the study by Upadhyay et al .…”
Section: Discussionmentioning
confidence: 99%